Polusi Udara dan Perkembangan Otak Anak: - Sofia, Norlaila; Aprilea, Noor Adha Aprilea Adha; Rusmilawaty, Rusmilawaty; Rizani, Khairir; As, Zulfikar Ali (Politeknik Kementerian Kesehatan Banjarmasin, 2025)
Air pollution is a global environmental problem that has the potential to have a negative impact on children's cognitive development. Scientific evidence suggests that exposure to air pollution, both during the prenatal and postnatal periods, is associated with neurodevelopmental disorders. This systematic literature review aims to synthesize scientific evidence on the influence of air pollution exposure on children's cognitive development, highlighting the prenatal period and school age. Literature searches were conducted through various scientific databases with keywords related to air pollution and children's cognitive development. The studies included in this review are longitudinal and cross-sectional studies published in the last ten years. The results of the review showed that exposure to air pollution, both during pregnancy and childhood, could negatively impact IQ, working memory, attention, and other neurological development. Some studies had also explored the socioeconomic and environmental factors that contribute to children's vulnerability to the harmful effects of air pollution. These studies emphasize the need for interventing to reduce pollution exposure and improve children's health. This evidence confirms the importance of mitigation efforts to reduce exposure to air pollution in pregnant women and children to support optimal cognitive development. More research is needed to understand the biological mechanisms as well as their long-term impacts.